Unconventional United Nations peacebuilding interventions in the 2014 Afghanistan elections and democratic transition (2018)
Following a request by the Afghanistan Government for assistance to support the country’s independent election body in conducting credible and acceptable election in 2014, a mandate was issued by the United Nations Security Council to support the democratic transition in the country. However, observers have described the outcome of the transition as unconventional. This study explored the core reasons for the unconventionality of the UN intervention in Afghanistan. Qualitative data were collected through interviews, observations and focus group discussions conducted in Kabul, Badakshan, Baghlan, Kunduz and Takhar provinces during the transition. The specific activities of the UN and its agencies in supporting the 2014 Afghan general elections and challenges encountered were unraveled. While a peaceful transfer of power did occur, the process that ended the transition was not democratic but political. The peculiarities of the country’s local context hence determined the outcome of the transition. Therefore, the transition project cannot be a model for future UN initiatives